Coverage of Acta Dermatovenerologica Alpina, Pannonica et Adriatica in Elsevier's CiteScore index - Poljak, Mario (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2017)
In December 2016, Elsevier launched a new tool that helps measure the citation impact of academic journals, called the CiteScore index. The CiteScore index values for 2015 confirmed the status of Acta Dermatovenerologica Alpina, Pannonica et Adriatica (Acta Dermatovenerol APA) as the leading journal in dermatology and sexually transmitted infections in the region. Sixty-five articles published in Acta Dermatovenerol APA from 2012 to 2014 received a total of 77 citations in 2015, resulting in a CiteScore index value of 1.18 for the journal. More than half of the articles published from 2012 to 2014 received at least one citation in 2015. Acta Dermatovenerol APA performed well in all three categories listed because it is ranked 384th out of 1,549 journals in the category General Medicine (75th percentile), 53rd out of 122 journals in the category Dermatology (56th percentile), and 142nd out of 246 journals in the category Infectious Diseases (42nd percentile).
Keywords: academic journals; akademske revije; citation; citiranje; dermatologija; dermatology